2017
DOI: 10.1080/10428194.2017.1344843
|View full text |Cite
|
Sign up to set email alerts
|

SH3BGRL as a novel prognostic biomarker is down-regulated in acute myeloid leukemia

Abstract: Phosphatase PRL-3 expression is positively associated to acute myeloid leukemia (AML) progression and drug resistance. SH3-domain-binding glutamic acid-rich protein-like protein (SH3BGRL), a downstream effector of PRL-3, plays a tumor suppressive role in solid tumors, but it remains elusive in AML. Here, we followed up and validated the relevance of SH3BGRL expression to AML progression in 116 cases. Results showed that SH3BGRL is down-regulated in 62.37% AML cases with poor prognosis. Cases with positive resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Our previous results unmasked a novel role of mouse SH3BGRL (mSH3BGRL) in driving colorectal cancer metastasis through c-Src activation, but the inverse role of human SH3BGRL as a tumor suppressor [16]. The later study further verified the suppression role of human SH3BGRL in leukemogenesis [17]. Clinically, SH3BGRL is highly upregulated in breast tumors and squamous oral carcinoma, implying its possible tumor-promoting role in these contexts [15,18,19].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our previous results unmasked a novel role of mouse SH3BGRL (mSH3BGRL) in driving colorectal cancer metastasis through c-Src activation, but the inverse role of human SH3BGRL as a tumor suppressor [16]. The later study further verified the suppression role of human SH3BGRL in leukemogenesis [17]. Clinically, SH3BGRL is highly upregulated in breast tumors and squamous oral carcinoma, implying its possible tumor-promoting role in these contexts [15,18,19].…”
Section: Introductionmentioning
confidence: 55%
“…However, SH3BGRL is observed to be broadly upregulated in breast tumors, including squamous oral carcinoma, among which only rare patients contain somatic mutation, such as R76C which can mimic the mouse SH3BGRL to enhance tumorigenesis and metastasis. In contrast, low SH3BGRL expression is related to AML progression [17], indicating the dual functions of SH3BGRL in cancer progression. Considering the adaptor character of SH3BGRL, this dual-sided effect might be attributed to the specific cell contexts in different tissues, including HER2 expression state in breast tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting, Wang et al suggested SH3BGRL may be an oncogene in mice, but as a tumor suppressor gene in human [8]. Xu et al found SH3BGRL as a novel prognostic biomarker is down-regulated in acute myeloid leukemia [9]. Our previous study and another group also found SH3BGRL3 could be as a biomarker in kidney and bladder cancer [10,11].…”
Section: Introductionmentioning
confidence: 62%
“…The DELs upstream of POU3F4 were also located downstream of SH3BGRL. SH3BGRL was reported to play a role in gastric cancer, acute myeloid leukemia and breast cancer [30][31][32]. However, whether DELs located between POU3F4 and SH3BGRL genes in uence the function of SH3BGRL remains unknown.…”
Section: Discussionmentioning
confidence: 99%